2017
DOI: 10.1002/jor.23748
|View full text |Cite
|
Sign up to set email alerts
|

BIO alleviated compressive mechanical force‐mediated mandibular cartilage pathological changes through Wnt/β‐catenin signaling activation

Abstract: Osteoarthritis induced by compressive mechanical force is characterized by decreased chondrocyte proliferation and degradation of the ECM. To examine underlying mechanisms of the pathological changes of mandibular cartilage induced by compressive mechanical force, an established animal model was used to examine Wnt signaling activation by glycogen synthase kinase-3 beta (GSK3β) inhibitor 6-Bromoindirubin-3'-oxime (BIO) injection in vivo. Histological changes in mandibular cartilage were assessed via hematoxyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…These pathological changes can be recovered by restoring the β-catenin signalling. 54 However, other authors found that mice with conditional F I G U R E 2 Pathways associated with chondrocyte death in TMJ osteoarthritis. Apoptosis and necroptosis are promoted in TMJ osteoarthritis, but the general trend of autophagy activity is inhibited β-catenin activation showed TMJ osteoarthritis-like phenotypes and up-regulation of MMP13 and ADAMT5 expression.…”
Section: Degenerative Changes In the Ecmmentioning
confidence: 99%
See 1 more Smart Citation
“…These pathological changes can be recovered by restoring the β-catenin signalling. 54 However, other authors found that mice with conditional F I G U R E 2 Pathways associated with chondrocyte death in TMJ osteoarthritis. Apoptosis and necroptosis are promoted in TMJ osteoarthritis, but the general trend of autophagy activity is inhibited β-catenin activation showed TMJ osteoarthritis-like phenotypes and up-regulation of MMP13 and ADAMT5 expression.…”
Section: Degenerative Changes In the Ecmmentioning
confidence: 99%
“…Compressive mechanical force reduces endogenous β‐catenin and leads to ECM degradation. These pathological changes can be recovered by restoring the β‐catenin signalling 54 . However, other authors found that mice with conditional β‐catenin activation showed TMJ osteoarthritis‐like phenotypes and up‐regulation of MMP13 and ADAMT5 expression 21,55 …”
Section: The Canonical Pathological Changes During the Tmj Osteoarthritismentioning
confidence: 99%
“…A study by Yuan reported that Wnt pathway inhibition by overload is characterized by OA manifestations such as induced ECM degradation, upregulated inflammatory factors, and trabecular bone erosion. The activation of the Wnt pathway can reverse these symptoms [38]. Physiological stress can activate Wnt signaling to inhibit osteoclast production and promote COL2A1 synthesis [39].…”
Section: The Wnt Pathwaymentioning
confidence: 99%
“…Interestingly, cWnt signaling has been recently shown to drive macrophages to the M2 subtype , and bioactive factors secreted by M2 macrophages have osteogenic effects on osteoprogenitors . In a recent study, BIO has also been shown to stimulate the proliferation of mandibular chondrocytes in vivo .…”
Section: Discussionmentioning
confidence: 99%